A mobile sense of place: exploring a novel mixed methods user-centred approach to capturing data on urban cycling infrastructure. Issue 4 (2nd October 2022) - Wesener, Andreas; Vallance, Suzanne; Tesch, Maike; Edwards, Sarah; Frater, Jillian; Moreham, Richard
ABSTRACT: The paper explores a user-centred methodology for collecting, categorising, visualising, and interpreting data on urban cycling infrastructure and related cycling events. It develops a mobile mixed methods approach combining audio, video, sensor, and geospatial data sources. The method responds to stakeholders' feedback and related concerns about negotiating engineering, landscape and urban design, planning and policy elements in a way that addresses cyclists' needs. It is tested in a pilot study that combines infrastructure monitoring and perception data collection on eight newly built Major Cycle Routes in Christchurch, New Zealand. Data from one Major Cycle Route is used to explore methods of data categorisation, visualisation and interpretation. Based on the results of the pilot study, the paper discusses potential methodological changes or additions. It suggests future research opportunities and potential applications of the proposed methodology to support stakeholders' efforts to advance the planning, design and implementation of urban cycleways.